2021
DOI: 10.1097/md.0000000000024830
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of low back pain and potential risk factors among pharmacists

Abstract: Low back pain (LBP) is one of the most common symptoms of work-related musculoskeletal disorders in pharmacists. This can impede the physical functions of the body and lead to incapacitation, resulting in significant social and economic burden. This study aimed to investigate the incidence and risk factors that correlate with LBP in Taiwanese pharmacists. A retrospective cohort study was conducted among all registered pharmacists aged 20 to 40 years using the National Health Insurance Research Datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The reported percentage goes in line with many studies conducted in different countries. This nding is attributed to similarity of work setting and health delivery system [7][8][9]. However, many other studies reported higher incidence of chronic pain [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The reported percentage goes in line with many studies conducted in different countries. This nding is attributed to similarity of work setting and health delivery system [7][8][9]. However, many other studies reported higher incidence of chronic pain [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, standing in a position for long durations is a long-term challenge to the functions of the body. It has been reported that low back pain (LBP) is one of the major symptoms of MSDs in pharmacists (37), and the incidence rate was 16.60%. Furthermore, in older pharmacists (28.49%; P < .01) and those who worked at district hospitals (23.51%; P < .01) revealed higher proportion of LBP.…”
Section: Wwwkjhskiuacug Kjhs 1: 2021 55mentioning
confidence: 99%
“…To prioritize some medicine packages, criteria such as their medical significance or cost might be applied. Moreover, the aforementioned action is monotonous, tedious, frequent and highly repetitive, due to the recurrent lifting and transferring of packages, and repeated hand/wrist motions to place the scan in the correct position and press the button to detect the Data Matrix code [24]. The addressed cases are common physical work-related risk factors that can cause upper limb musculoskeletal disorders to the operator [25], and therefore should be avoided.…”
Section: Introductionmentioning
confidence: 99%